Benchmarking care for very low birthweight infants in Ireland and Northern Ireland. Issue 1 (31st August 2009) - Murphy, B P; Armstrong, K; Ryan, C A; Jenkins, J G
Abstract : Background: Benchmarking is that process through which best practice is identified and continuous quality improvement pursued through comparison and sharing. The Vermont Oxford Neonatal Network (VON) is the largest international external reference centre for very low birth weight (VLBW) infants. This report from 2004–7 compares survival and morbidity throughout Ireland and benchmarks these results against VON. Methods: A standardised VON database for VLBW infants was created in 14 participating centres across Ireland and Northern Ireland. Results: Data on 716 babies were submitted in 2004, increasing to 796 babies in 2007, with centres caring for from 10 to 120 VLBW infants per year. In 2007, mortality rates in VLBW infants varied from 4% to 19%. Standardised mortality ratios indicate that the number of deaths observed was not significantly different from the number expected, based on the characteristics of infants treated. There was no difference in the incidence of severe intraventricular haemorrhage between all-Ireland and VON groups (5% vs 6%, respectively). All-Ireland rates for chronic lung disease (CLD; 15–21%) remained lower than rates seen in the VON group (24–28%). The rates of late onset nosocomial infection in the all-Ireland group (25–26%) remained double those in the VON group (12–13%). Discussion: This is the first all-Ireland international benchmarking report in any medical specialty. Survival, severe intraventricular haemorrhage and CLD compare favourably with international standards, but rates of nosocomial infection in neonatal units are concerning. Benchmarking clinical outcomes is critical for quality improvement and informing decisions concerning neonatal intensive care service provision.